Influence of Lenslet Configuration on Short-Term Visual Performance in Myopia Control Spectacle Lenses - Li, Xue; Ding, Chenglu; Li, Yuhao; Lim, Ee Woon; Gao, Yi; Fermigier, Bruno; Yang, Adeline; Chen, Hao; Bao, Jinhua (Frontiers in Neuroscience, 2021)
Purpose: This study aimed to evaluate short-term visual performance and optical quality of three different lenslet configurations on myopia control spectacle lenses. Materials and Methods: This study utilized a cross-over design. Distance visual acuity (VA) was measured in 50 myopic children; contrast sensitivity (CS) was measured in 36 myopic children. For each test, four spectacle lenses were evaluated in a random order: single-vision lens (SVL), lens with concentric rings of highly aspherical lenslets (HAL), lens with concentric rings of slightly aspherical lenslets (SAL), and lens with honeycomb configuration of spherical lenslets (HC). The modulation transfer function (MTF) and MTF area (MTFa) were used to determine optical quality. All tests were performed monocularly on the right eye with full correction. Results: HAL and SAL had larger MTFa than HC. VA in lenses with lenslets was significantly reduced compared to SVL (all p < 0.01). The reduction in VA was worse with HC than with SAL (p = 0.02) and HAL (p = 0.03); no effect of lenslet asphericity was found (p > 0.05). VA changes induced by lenslets showed no correlation with spherical equivalent refraction (all p > 0.05) and were weakly positively associated with age for SAL (r = 0.36, p = 0.01) and HC (r = 0.31, p = 0.03), but not for HAL (p = 0.30). The area under the log contrast sensitivity function (AULCSF) decreased with HAL and HC (all p < 0.001) in all illumination levels, and AULCSF with HAL was higher than that with HC in a photopic condition (1.17 ± 0.10 vs. 1.10 ± 0.13, p = 0.0004). The presence of lenslets did not affect CS at 3 cycles per degree (cpd) (p = 0.80). At 6 to 18 cpd, CS was significantly reduced by HAL and HC (all p < 0.05), but not SAL (p > 0.05) compared to SVL. At high spatial frequencies (>12 cpd) both SAL and HAL reduced CS significantly less than HC (all p < 0.01). Conclusion: Short-term visual performance was minimally impaired by looking through the lenslet structure of myopia control spectacle lenses. Concentric rings with aspherical lenslets had a significantly lower impact on both VA and CS than honeycomb configuration with spherical lenslets.